2022
DOI: 10.3390/molecules27134302
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Identification and Structural Characterization of Compounds from Plantago asiatica L. by Liquid Chromatography-Mass Spectrometry Combined with Ion Mobility Spectrometry

Abstract: Plantago asiatica L. (PAL) as a medicinal and edible plant is rich in chemical compounds, which makes the systematic and comprehensive characterization of its components challenging. In this study, an integrated strategy based on three-dimensional separation including AB-8 macroporous resin column chromatography, ultra-high performance liquid chromatography–quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF MS), and ultra-high performance liquid chromatography-mass spectrometry with ion-mobility spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 41 publications
(43 reference statements)
1
25
0
Order By: Relevance
“…Thus, based on LC/MS data, compound 1 was tentatively identified as caffeic acid-O-deoxyhexosylhexoside. (44 Da) and cleavage of a hexose (hex) moiety (162 Da), corresponding to the fragmentation behavior of iridoids [19][20][21] (S4, Supplementary Information). The mass spectrum observed in the AcOEt fraction exhibited fragment ions at m/z 193 [MÀ Hhex-H 2 O] À and 149 [MÀ H-hex-H 2 OÀ CO 2 ] À , that matched with geniposidic acid or secologanic acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, based on LC/MS data, compound 1 was tentatively identified as caffeic acid-O-deoxyhexosylhexoside. (44 Da) and cleavage of a hexose (hex) moiety (162 Da), corresponding to the fragmentation behavior of iridoids [19][20][21] (S4, Supplementary Information). The mass spectrum observed in the AcOEt fraction exhibited fragment ions at m/z 193 [MÀ Hhex-H 2 O] À and 149 [MÀ H-hex-H 2 OÀ CO 2 ] À , that matched with geniposidic acid or secologanic acid.…”
Section: Resultsmentioning
confidence: 99%
“…The fragmentation patterns of verbascoside, [39] are presented in S7 (Supplementary information). According to their different Rt and references, [20,62] compound 11 which eluted first was identified as acteoside and compound 13 which eluted second as isoverbascoside. [20,54,55] The observed fragments do not correspond with those provided in literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies on the chemical composition of TCM had combined multilevel high‐resolution MS and online energy‐resolved MS to distinguish isomers with the same fragment ions and some differences in fragment relative abundance using different compounds with different on‐line collision energy (OCE) (Tang et al, 2021). Alternatively, MS with offline NMR, 1D‐NMR, and 2D‐NMR, and ion mobility MS could also be used to identify substances without reference standards (Gao et al, 2022; Nöst et al, 2021; Wang et al, 2016). It was obvious that the combination of multiple techniques could identify more compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the phytochemical composition of other Plantago species revealed similar components to those found in Plantago major, such as phenol, benzofuran, Diglycerol, various kinds of acids etc. (Jamilah et al 2012;Gao et al 2022).…”
Section: Phytoconstituents Of P Majormentioning
confidence: 99%